(3CNHGQ eUQ haVGFdgG hYLGFHgG hWQGFagG hZQGFHgG heG HgG ef GdHbGY hGdBKGQ hSjQ ef MdgG ef GdCFeIs - (3YR Gdedc eMeO Hf YHO Gddg Hf CMeO Hf ESeGYjd Hf YHO GdYRjR GdeSHMjs
(3ChdgG (B:s
( (3jHOC HHbjI SfI CQHY YTQI hCQHY eGFI (B) s
(3BNQgG (B:s
(3hML HGdfGS ai gPg GdSfI CHh Ydi GdMSf Hf YHO Gddg Hf GHQGgje GdMSjfi hcGf eHdZ bjGS Gdfjd GdbOje ai gPg GdSfI ai GdbYQ Je GdLRA GdCQHYhf ef CNHGQ eUQ haVGFdgG hYLGFHgG hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3HChdgG Jedc HGSe eMeO Hf eMeO GdJhUQi heWGdYI HGSe CMeO Hf YHO Gddg Hf GdMSf GdChMOi HGdbGgQI SfI (B853(3g`s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(534) s
Keywords: (3GdJGQjNs